Quantum-like model of partially directed evolution. (May 2017) - Melkikh, Alexey V.; Khrennikov, Andrei
Abstract: The background of this study is that models of the evolution of living systems are based mainly on the evolution of replicators and cannot explain many of the properties of biological systems such as the existence of the sexes, molecular exaptation and others. The purpose of this study is to build a complete model of the evolution of organisms based on a combination of quantum-like models and models based on partial directivity of evolution. We also used optimal control theory for evolution modeling. We found that partial directivity of evolution is necessary for the explanation of the properties of an evolving system such as the stability of evolutionary strategies, aging and death, the presence of the sexes. The proposed model represents a systems approach to the evolution of species and will facilitate the understanding of the evolution and biology as a whole.